The Association of Vitamin D Deficiency with Disease Activity in Rheumatoid Arthritis: A Systematic Review - Caroline Johansyah; I Putu Oka Yudaswara Pande; Maria Johansyah (International Medical Journal Corp. Ltd, 2025)
Introduction: Rheumatoid Arthritis (RA) is a chronic, systemic autoimmune disease characterized by persistent synovitis. Vitamin D, a secosteroid hormone with potent immunomodulatory properties, is frequently observed to be deficient in this patient population. This systematic review aims to comprehensively evaluate and synthesize the evidence linking vitamin D deficiency to the multifaceted measures of disease activity in RA. Methods: A systematic literature search was conducted across PubMed, Google Scholar, Semantic Scholar, Springer, Wiley Online Library for observational studies published up to December 2024. Studies were included if they assessed serum 25-hydroxyvitamin D levels and at least one validated measure of disease activity in adult patients with RA. Data on study characteristics and over 15 distinct clinical, laboratory, and patient-reported outcomes were extracted. The methodological quality and risk of bias of included studies were assessed using the Cochrane ROBINS-I (Risk Of Bias In Non-randomized Studies – of Interventions) tool. Results: Seventeen observational studies, comprising a total of 5,618 RA patients, met the inclusion criteria. The findings revealed a high prevalence of vitamin D deficiency and insufficiency across diverse RA cohorts. A statistically significant inverse correlation between serum 25(OH)D levels and the Disease Activity Score in 28 joints (DAS28) was the most consistent finding across the majority of studies. Furthermore, lower vitamin D levels were significantly associated with higher levels of inflammatory markers, including Erythrocyte Sedimentation Rate (ESR) and C-Reactive Protein (CRP), increased tender and swollen joint counts, and worse patient-reported outcomes such as pain, functional disability (Health Assessment Questionnaire), and reduced quality of life. Discussion: The synthesized evidence strongly supports an association between lower vitamin D status and heightened disease activity in RA. This relationship is biologically plausible, given vitamin D's established role in suppressing pro-inflammatory Th1/Th17 pathways and promoting regulatory T-cell function, both of which are central to RA pathogenesis. While the cross-sectional nature of most studies precludes definitive causal inference, the data suggest a potential bidirectional relationship where deficiency may contribute to immune dysregulation, and active disease may in turn exacerbate the deficiency. Conclusion: A substantial body of evidence demonstrates a significant association between vitamin D deficiency and higher disease activity across multiple domains in RA. These findings underscore the clinical importance of monitoring and correcting vitamin D status in patients with RA, which may serve as a valuable, low-cost adjunct to standard therapeutic strategies to help mitigate the overall disease burden.